2014
DOI: 10.5964/jspp.v2i1.323
|View full text |Cite
|
Sign up to set email alerts
|

Political Left and Right: Our Hands-On Logic

Abstract: The origins and immediate vitality of the left/right divide which emerged in French revolutionary politics from 1789 can only be understood against the background of a much older classification dynamic based on the primacy of the right hand, first described by Robert Hertz in 1909. This dynamic infused political thinking first in Versailles and since 1815 in democracies throughout the world. In the process, the classical left/right polarity acquired a new dimension: the complementary notions of ‘accepting’ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Importantly however, recent large-scale cross-national research using World Value Survey data found that cultural and economic political attitudes on average are weakly related, and that it is more common for them to be negatively rather than positively related (Malka et al, 2019). These findings suggest that the relationship between economic and cultural dimensions may be context-dependent and inevitably emphasize the longstanding problem of the universality of the left-right distinction (Bienfait & van Beek, 2014).…”
Section: The Underpinnings Of Left-and Right-wing Political Orientationmentioning
confidence: 88%
See 1 more Smart Citation
“…Importantly however, recent large-scale cross-national research using World Value Survey data found that cultural and economic political attitudes on average are weakly related, and that it is more common for them to be negatively rather than positively related (Malka et al, 2019). These findings suggest that the relationship between economic and cultural dimensions may be context-dependent and inevitably emphasize the longstanding problem of the universality of the left-right distinction (Bienfait & van Beek, 2014).…”
Section: The Underpinnings Of Left-and Right-wing Political Orientationmentioning
confidence: 88%
“…Yet, Sartre called it an "empty vessel" (Bobbio, 1996), and many others accused it of either oversimplifying complex political phenomena or of being unable to capture newly rising social clashes, for example, recent reactions to issues surrounding climate change and environment conservation (Giddens, 1994). However, the concept is still widely used in social sciences due to its simplicity and versatility (Inglehart, 1990;Bienfait & van Beek, 2014).…”
Section: Left-right Metaphormentioning
confidence: 99%